REMATTOOL-R - Machida, Lewis; Huerta Rodriguez, Francisco; Makumbi, Dan; Tarusenga, Murisi (2022)
REMATTOOL-R is a tool that helps breeders to visualize and assess the relationship between yield and several agronomic traits. Users can download the application, an abstract of the paper describing the application, and a sample dataset. The sample dataset includes maize field trial result means of an experiment from the Water Efficient Maize for Africa (WEMA) Project funded by the Bill and Melinda Gates Foundation (BMGF, Grant # OPP1019943) and the Howard Buffet Foundation. The tabulated means are from data obtained from five locations across Kenya.